The monitoring of hematopoietic stem cell transplant donors and recipients from endemic areas for malaria - Inoue, Juliana; Machado, Clarisse Martins; Lima, Giselle Fernandes Maciel de Castro; Nascimento, Maria de Jesus Costa; Colturato, Vergílio Rensi; Di Santi, Silvia Maria (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Malaria is an unusual complication after hematopoietic stem cell transplantation in non-endemic countries. However, transplant candidates, recipients and donors living in endemic regions frequently report previous episodes of malaria. This fact could represent an important risk for immunosuppressed recipients that could develop severe malaria cases. We report a case of hematopoietic stem cell transplant (HSCT) in which the donor had a history of previous malaria, and close monitoring was performed before and after procedure by parasitological and molecular tests. The donor presented Plasmodium vivax in thick blood smears one month after transplant and was treated according to Brazilian Health Ministry guidelines. The polymerase chain reaction (PCR) was able to detect malaria infection in the donor one week earlier than thick blood film. Even without positive results, the recipient was pre-emptively treated with chloroquine in order to prevent the disease. We highlight the importance of monitoring recipients and donors in transplant procedures with the aim of reducing the risk of malaria transmission.